RESEARCH ON ANIMAL PRODUCTION TRENDS IN 2014-2020 IN ROMANIA - Andreea Daniela GIUCĂ; Ana URSU; Cristina Maria STERIE; Dalila Gabriela STOICA; Laurențiu Ionuț PETRE (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper aims to analyze the actual trends in animal production in Romania. The statistical data were provided by the National Institute of Statistics for the period 2014-2020, and in order to highlight the evolution trends, the following statistical indicators were calculated: arithmetic mean, standard deviation, coefficient of variation and annual growth rate. The species with the most livestock in 2020, in Romania is represented by poultry (71,183,431 heads), of which adult laying birds (36,648,478 heads); cattle (1,875,169 heads), of which cows, buffaloes and heifers (1,230,717 heads,) and sheep (10,281,473 animals). Regarding animal production, we have the following statistical data: the live weight of cattle for slaughter was 172,586 tons, by approx. 6% lower than in 2014, pigs live weight decreased by 7%, reaching 498,098 tons in 2020. Finally, the live weight of sheep and goats increased by 12% during the period under review, reaching 120,571 tonnes in 2020. The largest increase of 36% was noticed in poultry live weight.